1993
DOI: 10.1111/j.1365-2796.1993.tb00724.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of mitochondrial abnormality in skeletal muscle of patients with iron‐deficient anaemia

Abstract: Mitochondrial ATP synthesis was not limited by oxygen supply or an intrinsic mitochondrial defect. Therefore, the reduced exercise capacity seen in iron deficiency could be due to central causes and not to skeletal muscle metabolic abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Acute and chronic anemia are associated with increased arterial lactate concentrations for a given metabolic rate (18);and more specifically, graded reduction in [Hb] is associated with increased skeletal muscle lactate output during exercise (17). However, there are no differences in resting or exercise skeletal muscle pl-l, as a function of anemia in rat (19) or human (20). Finally, no relationship was found between [Hb] and either resting pl-l, or its threshold in the current study.…”
Section: Discussionmentioning
confidence: 96%
“…Acute and chronic anemia are associated with increased arterial lactate concentrations for a given metabolic rate (18);and more specifically, graded reduction in [Hb] is associated with increased skeletal muscle lactate output during exercise (17). However, there are no differences in resting or exercise skeletal muscle pl-l, as a function of anemia in rat (19) or human (20). Finally, no relationship was found between [Hb] and either resting pl-l, or its threshold in the current study.…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, some observational studies on IDA in humans have failed to confirm the associations between ID and muscle dysfunction. For example, Thompson et al investigated skeletal muscle bioenergetics in women with IDA using P magnetic resonance spectroscopy, and have not documented significant mitochondrial abnormality . Furthermore, Celsing et al investigated the biochemical properties of skeletal muscle samples obtained from subjects with chronic moderate to severe IDA and controls, and have demonstrated that the maximal activities of glycolytic and oxidative enzymes in these two groups were similar .…”
Section: Links Between Iron Deficiency Decreased Exercise Capacity mentioning
confidence: 99%
“…For example, Thompson et al investigated skeletal muscle bioenergetics in women with IDA using 31 P magnetic resonance spectroscopy, and have not documented significant mitochondrial abnormality. 77 Furthermore, Celsing et al investigated the biochemical properties of skeletal muscle samples obtained from subjects with chronic moderate to severe IDA and controls, and have demonstrated that the maximal activities of glycolytic and oxidative enzymes in these two groups were similar. 78 Importantly, the aforementioned studies were observational only and the study groups were relatively small.…”
Section: Iron Deficiency Global Exercise Capacity and Skeletal Muscmentioning
confidence: 99%
“…Iron homeostasis in mitochondria also differs from that in the cytoplasm. Iron deprivation affects mitochondrial iron enzymes less than cytosolic iron enzymes (21). By contrast, excess iron is not usually deposited in mitochondria but is deposited in the cytosol as ferritin.…”
mentioning
confidence: 98%